Usability Testing of the Metadata Management of Audio Archive - Pribadi, Joni Dwi; Wijayanti, Rena Feri; Armayrishtya, Zhulvardyan; Dhakirah, Sanita; Mufarikhatin, Khoiri (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The aim of this research is to test the usability of the audio archive metadata management application. This application is used to record all song collection data in the form of cassettes and vinyl and is also used to search for collection data easily and quickly. This research used System Usage Scale (SUS) method to test the application usability. The SUS Testing was carried out by distributing a questionnaire which consists of 10 statements to 30 respondents to determine the assessment scale based on percentile rank, grade, adjective rating, acceptability, and net promoter score. The result of the system usage scale testing showed an average total score of 83. By detail, this result explained that the percentile range assessment scale is between 90-95%, grade is A, adjective rating is in the Excellent category, acceptability is in the acceptable category, and net promoter is in the promoter category. Thus, it can be concluded that the audio archive metadata management application is suitable for use as a search and retrieval tool for song collections in the form of cassettes and vinyl. However, in order to increase the application’s usefulness, the application can be more developed in the future by adding additional features to meet the criteria as a better metadata management tool.